The face and emotions in the Hebrew Bible - Kruger, Paul Albertus (Old Testament essays, 2005)
This contribution presents a semantic analysis of how the face and certain emotions are related in the Hebrew Bible. It focuses on the conventionalised linguistic descriptions in Biblical Hebrew, namely expressions and idioms that contain the face and other parts of the body associated with it (e g eyes, nose, mouth, teeth, etc), and the role they play in the conceptualisation of emotions. It is found that the face, with its associated parts, is most expressive in the communication of certain central emotions which have a bodily or psychological basis, such as anger, fear, joy, disgust and depression.